Anaerobic Digestion of Slaughterhouse Wastewater: CO2 Capture of Biogas Using Chlorella vulgaris - Nur Indradewi Oktavitri; Wahyu Budi Pratiwi; Indah Purnamasari; Mufrihatul Hayati; Mega Rosita Fitrianingtyas; Semma Hadinnata (Universitas Gadjah Mada, 2019)
Biogas quality from anaerobic digester influenced the combustion of biogas. A high percentage of CO2 in biogas indicates the low quality of biogas. Abatement of CO2 using microalgae, such as Chlorella vulgaris could enhance the quality of biogas. The aim of this research was to observe the ability of C. vulgaris on CO2 removal from slaughterhouse wastewater biogas. In this research, two anaerobic digesters were provided with the different condition of biogas collector bag. The first digester was combined with only biogas collector bag, while another digester was combined with C. Vulgaris. Slaughterhouse wastewater volume in each digester was 3.5 L. Observation time was 15 days and the samples were collected for every 5 days. The result showed that anaerobic digester was able to remove 63% of COD. Biogas composition of slaughterhouse wastewater after incubation for 15 days was 52.70% of air, 46.85% of CH4and 0.45% of CO2. C. Vulgaris enhanced CO2 removal from biogas up to 7%. The density of C. vulgaris decreased to 51 cell/mL. The biogas composition was probably influenced by the density of C. vulgaris.